Increase Student Learning Activities by Using A Problem-Based Learning Model in Legum Technology Lecture Materials - Almira Ulimaz; Jesi Yardani; Dewi Amelia Widiyastuti (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
Student learning activities can be measured by how active students are while studying. A student-centered learning model is needed, especially for courses with no practicum, such as legum technology material, to make the classroom atmosphere more varied. Therefore, this study aims to increase student learning activities using a problem-based learning model in legum technology lecture materials. This research is a class action study conducted in 2 cycles, each consisting of 2 meetings. The research subject comprised 20 students majoring in Agricultural Industrial Technology, Agro-industrial Study Program. The data collection techniques include preserving student learning activities using a problem-based learning model. The results showed that the students learning activity increased with an average per cycle in cycle I of 2.14 and was included in the "sufficient" category with the description of group C, and on average in cycle II increased with the achievement of 2.85 and has been included in the "good" category. This research shows that the problem-based learning model has been proven to improve student learning activities in the classroom. In addition, this research also demonstrates that classroom action research can be carried out in elementary, middle, and high schools and at the college level.